2013
DOI: 10.1097/mop.0b013e328364b8a7
|View full text |Cite
|
Sign up to set email alerts
|

Novel initiatives of the National Institutes of Health to support congenital heart disease research

Abstract: Purpose of review In fiscally challenging times, scientists must seek creative strategies and leverage existing resources to advance research. Recent findings This review describes programmes supported by the National Heart, Lung, and Blood Institute (NHLBI) of the National Institutes of Health (NIH) to promote research in paediatric cardiology and congenital heart disease (CHD). Summary An understanding of NHLBI-supported research programmes will help investigators identify opportunities to collaborate wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…To address these concerns, the Paediatric Heart Network (PHN) was established in 2001 by the National Heart, Lung and Blood Institute, using an investigator-led model of core clinical centres and auxiliary sites across the USA and Canada [ 4 , 17 ]. Policies and procedures are developed by a Central Steering Committee, with representation from all participating centres, and implemented by a Data Coordinating Centre, with scientific and safety oversight provided by Protocol Review Committee and DMC, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these concerns, the Paediatric Heart Network (PHN) was established in 2001 by the National Heart, Lung and Blood Institute, using an investigator-led model of core clinical centres and auxiliary sites across the USA and Canada [ 4 , 17 ]. Policies and procedures are developed by a Central Steering Committee, with representation from all participating centres, and implemented by a Data Coordinating Centre, with scientific and safety oversight provided by Protocol Review Committee and DMC, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The landmark Single Ventricle Reconstruction (SVR) trial randomized 555 infants with single-ventricle lesions (84% of those eligible) to the Norwood procedure, with either a modified Blalock–Taussig shunt or a right ventricle to pulmonary artery shunt across 15 sites in just over 3 years [ 9 ]. This trial demonstrated not only the power of collaboration to increase sample size in a rare condition but also that surgeons and parents were willing to randomize children to different treatments, even in high-risk complex neonatal cardiac surgery, when there is clinical equipoise [ 17 ]. To date, it has produced more than 20 publications including a publicly available data set and remains the only Phase III trial in children’s heart surgery to demonstrate a difference in 1-year transplant-free survival [ 9 ]; perhaps, more importantly, this difference was lost by 3 years [ 20 ], and further follow-up is keenly awaited.…”
Section: Discussionmentioning
confidence: 99%
“…Companion diagnostics for specific cardiovascular diseases will advance our ability to realize the promise of personalized medicine [60]. To this end, the pediatric cardiology research community is in an excellent position to leverage consortia that combine genomics with patient care [61]. The Pediatric Cardiac Genomics Consortium (PCGC) is linked to the Pediatric Heart Network (PHN) and therefore is in a position to apply combined genetic information and predictive biomarkers to new clinical trials.…”
Section: Discussionmentioning
confidence: 99%